Co-Creation in Urban Governance: From Inclusion to Innovation - Hedensted Lund, Dorthe (Scandinavian Journal of Public Administration, 2018)
This article sets out to establish what we mean by the recent buzzword ‘co-creation’ and what practical application this concept entails for democracy in urban governance, both in theory and practice. The rise of the concept points to a shift in how public participation is understood. Whereas from the 1970s onwards the discussions surrounding participation centred on rights and power, following Sherry Arnstein, participation conceptualised as co-creation instead focuses on including diverse forms of knowledge in urban processes in order to create innovative solutions to complex problems. Consequently, democratic legitimacy now relies to a much greater extent on output, rather than input legitimacy. Rather than provision of inclusive spaces for democratic debate and empowerment of the deprived, which have been the goals of numerous urban participatory efforts in the past, it is the ability to solve complex problems that has become the main criterion for the eval- uation of co-creation. Furthermore, conceptualising participation as co-creation has con- sequences for the roles available to both citizens and public administrators in urban pro- cesses, which has implications for urban governance. An explicit debate, both in academ- ia and in practice, about the normative content and implications of conceptualising partic- ipation as co-creation is therefore salient and necessary.